2019
DOI: 10.1155/2019/3108093
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick Disease: An Underdiagnosed Lysosomal Storage Disorder

Abstract: Lysosomal storage disorders (LSDs) collectively constitute a significant public health burden in developing countries. Commoner LSDs include Gaucher, Fabry, and Niemann-Pick disease (NPD), but many cases remain undiagnosed. With the high incidence of consanguineous marriages, South East Asian countries are expected to have high prevalence of these LSDs. Here we report 4 cases of NPD type A/B in 3 families presenting with hepatosplenomegaly and cytopenias including one family with two sibs having hypertension a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…These morphologic findings were consistent with the patient's ECG study suggestive of left ventricular hypertrophy. While we did not have the opportunity to examine the pathology of the patient's heart valves, it is worth mentioning that the tricuspid and mitral valve regurgitation observed here in the echocardiogram study at age 21 months has been observed by others reported in the ASMD literature [ 4 ], suggesting that there may be a link between the findings and disease-related substrate accumulation.
Fig.
…”
Section: Resultsmentioning
confidence: 55%
“…These morphologic findings were consistent with the patient's ECG study suggestive of left ventricular hypertrophy. While we did not have the opportunity to examine the pathology of the patient's heart valves, it is worth mentioning that the tricuspid and mitral valve regurgitation observed here in the echocardiogram study at age 21 months has been observed by others reported in the ASMD literature [ 4 ], suggesting that there may be a link between the findings and disease-related substrate accumulation.
Fig.
…”
Section: Resultsmentioning
confidence: 55%
“…These nanocarriers are capable of forming complexes with cholesterol which in turn slows the progress of the disease. Many researchers are studying the various forms of these compounds in their use to address this pathology [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various reviews and reports consequently appear to be in consensus that further research is needed from which an appropriate conclusion can be drawn for potential therapies and diagnostic methods [ 10 , 11 ]. This case report shall seek to highlight the case presentations of this rare disease so that the issue of under-diagnosis can be more readily addressed [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Types A and B result from the deficient activity of sphingomyelinase and the SMPD1 gene located on bands 11p15.1-p15.4 and are referred to as acid sphingomyelinase deficiency (ASMD). 8 Type C is a neuronopathic form that results from defective cholesterol transport. 1 The most common form of Niemann pick disease is Type A, i.e., Acute neuropathic form which presents in the first months of life with marked hepatosplenomegaly, lymphadenopathy and psychomotor retardation, followed by neurodevelopmental regression.…”
Section: The Casementioning
confidence: 99%